1967
DOI: 10.1063/1.1701544
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Frequencies and Intensities of the Lattice Vibrations of Thiourea and Thiourea-d4

Abstract: Articles you may be interested inLattice vibrations of semirigid molecules: Low-frequency vibrations of 4,4-difluorobenzophenone and 4,4dichlorobenzophenone J. Chem. Phys. 106, 9505 (1997); 10.1063/1.473852 Vibrational calculations on the biphenyl crystal: The mixing between low frequency internal and lattice modesFrequencies of the lattice vibrations~of .. the room-temperature modification of thiourea and deuterated thiourea have been calculated assuming a simple force field. The calculated frequencies are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Lattice dynamical calculation (Takahashi, Schrader, Meier and Gottlieb, 1967) has shown that the soft-mode eigenvector consists mainly of a polar molecular libration about the c axis combined with a nonpolar translation along the a axis (see also .…”
Section: Thioureamentioning
confidence: 98%
“…Lattice dynamical calculation (Takahashi, Schrader, Meier and Gottlieb, 1967) has shown that the soft-mode eigenvector consists mainly of a polar molecular libration about the c axis combined with a nonpolar translation along the a axis (see also .…”
Section: Thioureamentioning
confidence: 98%
“…All data required for the calculation are taken from the work of Takahashi et el. [19]. These authors have also calculated the transformation matrix A, which is also needed for the calculation.…”
Section: P(w K ) = ~-(And(wk) -I) E ( W K )mentioning
confidence: 99%